IMPLEMENTASI DIGITAL PUBLIC RELATIONS MELALUI MEDIA SOSIAL TIKTOK @INFOBANKOFFICIAL DALAM MEMPERKUAT BRAND IMAGE PT INFOBANK MEDIA GROUP - Muhammad Mahesa Rizieq Akbar; Tria Patrianti (PT. Hasba Edukasi Mandiri, 2025)
This research aims to analyze the implementation of Digital Public Relations (Digital PR) conducted by PT Infobank Media Group through its official TikTok account, @InfobankOfficial, in strengthening its brand image as a credible, educational, and adaptive financial media institution in the era of digital communication. The phenomenon stems from the shifting information consumption patterns of the younger generation, who are increasingly active on short-form video platforms such as TikTok. This study employs a qualitative descriptive case study method. Data were collected through in-depth interviews with three key informants (Business Development Manager, Social Media Specialist, and Assistant Manager of Infobank), two external triangulators, and direct observation of @InfobankOfficial TikTok content. Data were analyzed through stages of reduction, presentation, and conclusion drawing. The findings reveal that Infobank implements a Digital PR strategy by utilizing TikTok’s features—short videos, viral sounds, educational captions, and interactive tools—to deliver financial literacy messages in an engaging and easily digestible way. The use of two-way communication and adaptation to social media trends proved effective in increasing user engagement and strengthening the public perception of Infobank’s brand image as a modern, professional, and responsive financial media institution. This study highlights the importance of integrating creative content with educational value in Digital PR strategies to build a positive reputation and sustain audience trust in the digital communication era.